The biological performance of purified supercoiled p53 plasmid DNA in different cancer cell lines. (December 2018) - Valente, J.F.A.; Sousa, A.; Gaspar, V.M.; Queiroz, J.A.; Sousa, F.
Graphical abstract: Highlights: Purified p53-pDNA can re-establish the p53 function, controlling cancer progression. L -Methionine affinity matrix successfully purified the supercoiled (sc) p53-pDNA. Apoptosis induced by sc p53-pDNA was assessed in different malignant and non-malignant cell lines. The biological performance of pure sc p53 pDNA was higher than that of native samples. Abstract: Tumor suppressor p53 remains one of the most interesting therapeutic targets in cancer gene therapy due to its consistent mutation in numerous cancers. Thus, the reinstatement of the p53 expression and function can be seen as an effective alternative for cancer treatment, motivating research in this field. In this study, l -methionine matrix was used to purify the supercoiled topoisoform of a plasmid DNA encoding the p53 protein. This pure biopharmaceutical was conjugated with liposomes to comprehensively analyze its in vitro performance and therapeutic potential in different cancer cell lines, including the lung and cervix models. A different profile of cellular responses was attained after the transfection of these cancer cell lines with the p53-pDNA. Actually, the in vitro transfection with pure sc p53-pDNA resulted in a higher expression of the tumor suppressor protein in cancer cells when compared with the native pDNA samples (oc + sc topoisoforms). Also, wild-type p53 expression following transfection was significantly higher in HeLa cervix cancer cells compared to that obtained in A549 lung cancer cells. Overall, our findings emphasize the potential of sc pDNA gene-based therapy, also raising awareness of the need to adjust the therapeutics, considering the feature of high heterogeneity of cancer cells.